Association Between Serum Osmolality and Acute Kidney Injury in Critically Ill Patients: A Retrospective Cohort Study - Yang, Jie; Cheng, Yisong; Wang, Ruoran; Wang, Bo (Frontiers in Medicine, 2021)
Purposes: Acute kidney injury (AKI) is a common complication in critically ill patients and is usually associated with poor outcomes. Serum osmolality has been validated in predicting critically ill patient mortality. However, data about the association between serum osmolality and AKI is still lacking in ICU. Therefore, the purpose of the present study was to investigate the association between early serum osmolality and the development of AKI in critically ill patients. Methods: The present study was a retrospective cohort analysis based on the medical information mart for intensive care III (MIMIC-III) database. 20160 patients were involved in this study and divided into six subgroups according to diagnosis on admission causes for ICU admission. The primary outcome was the incidence of AKI after ICU admission. The association between early serum osmolality and AKI was explored using univariate and multivariate logistic regression analyses. Results: The normal range of serum osmolality was 285-300mmol/L. High serum osmolality was defined as serum osmolality >300mmol/L and low serum osmolality was defined as serum osmolality <285mmol/L. Multivariate logistic regression indicated that high serum osmolality was independently associated with increased development of AKI with OR=1.198 (95%CL=1.199-1.479, P<0.001) and low serum osmolality was also independently associated with increased development of AKI with OR=1.332 (95%CL=1.199-1.479, P<0.001), compared with normal serum osmolality respectively. Conclusions: In critically ill patients, early high serum osmolality and low serum osmolality were both independently associated with an increased risk of development of AKI.